Impact of Tower Spacing on the Performance of Multiple Natural Draft Dry Cooling Towers Under No Wind Conditions - Khamooshi, M; Anderson, TN; Nates, R (Department of Mechanical Engineering, Auckland University of Technology and Department of Mechanical Engineering, University of Auckland, 2017)
INTRODUCTION Natural draft dry cooling towers (NDDCT) are an important part of concentrated solar power (CSP) plants in that they dictate the flow of air over the condenser. Under no wind conditions, airflow in the NDDCT is driven by natural convection resulting in a relatively uniform temperature and pressure distribution in the condenser. By expanding CSP plants, additional cooling towers are needed to increase the cooling capacity of the plant and hence the layout of multiple cooling towers could influence the thermo-flow characteristics of these NDDCTs. Despite this previous studies have tended to focus on a single isolated cooling tower. In their work Lu et al. [1, 2] focused on improving the design of a small NDDCT with a tower aspect ratio of 1.25 using numerical simulations of a single NDDCT with and without the wind. In addition, they showed that windbreaks resulted in significant variation in the system performance. However, the question of how multiple small cooling towers interact with each other under the no-wind condition appears to have been overlooked.